Evolution of caesarean sections in Peru, an element to be evaluated - Munares-García, Oscar (2023)
In Peru, as in other parts of the world, the proportion of deliveries by cesarean section is considered high, with respect to the reference pattern of the World Health Organization (WHO) of 15%. For example, in Paraguay, 36.28% was found, in a public hospital in Lima, it reached 50.2%, and in Spain, in an autonomous community of Andalusia, it reached 24.8%. The reasons why caesarean section rates have increased in the world are variable, several factors have been determined, among them we have multiple pregnancies, previous caesarean section, higher socioeconomic status, among others. The objective is to evaluate some characteristics of cesarean deliveries in Peru and how they have evolved in a five-year period.